Koncepcje i modele konsolidacji a efektywność w polskiej energetyce - Brzóska, Jan; Pyka, Jan (Conceptions and Models of Consolidation and the Effectiveness of the Polish Energy Market, 2006)
One of the important goals of energy market's liberalization for the sector's companies is the growth of economic effectiveness. In the article the effectiveness of the national energy sector has been estimated. The main points of interest were benchmarking and structural comparison of basic effectiveness markers for Polish and leading European companies. New concepts and models of consolidation that should increase attractiveness and effectiveness of Polish energy market have been described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 419-429